2006
DOI: 10.2105/ajph.2005.062620
|View full text |Cite
|
Sign up to set email alerts
|

A System for Rapidly and Accurately Collecting Patients’ Race and Ethnicity

Abstract: Collecting race/ethnicity data using patients' own racial/ethnic categories is feasible with the use of computerized systems to capture verbatim responses and results in lower rates of missing and unusable data than do standard questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…30 Our survey findings are consistent to prior surveys of cardiovascular specialists in some respects but different in others. Like our survey, prior studies of cardiovascular specialists found a substantially higher proportion acknowledging racial differences in cardiac care among patients nationally (34%) than among patients they personally treat (5%).…”
Section: Discussionsupporting
confidence: 89%
“…30 Our survey findings are consistent to prior surveys of cardiovascular specialists in some respects but different in others. Like our survey, prior studies of cardiovascular specialists found a substantially higher proportion acknowledging racial differences in cardiac care among patients nationally (34%) than among patients they personally treat (5%).…”
Section: Discussionsupporting
confidence: 89%
“…Eligibility Criterion 2 was chosen because self-identification of race/ethnicity by research participants has been shown to be feasible, efficient, accurate, and to result in lower rates of missing and unusable data than do standard questions [22]. …”
Section: Methodsmentioning
confidence: 99%
“…In the United States where intermarriage and intermingling of health behaviors is common the strength of an individual’s self-identified ethnic identity may be a more significant determinant of behavior than the individual’s actual ethnicity (Baker et al, 2006). However, the discrepancies between interviewer data on self-identity and self-report mentioned earlier may stem in part from the use of forced categories that do not always match the words that patients would use to identify themselves.…”
Section: Challenges In Collecting Self-identity Of Race and Ethnicitymentioning
confidence: 99%